“The Other Problem— That of the Woman with Children”: Vera Brittain, Maternal Work, and the Politics of Leaning In - Podnieks, Elizabeth (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
Tensions and battles about career and children, which inform our contemporary“mommy wars,” were equally the driving forces for many first-wave feminists who contested traditional conceptions of wifehood and motherhood. One of the most outspoken figures from this past era, and my focus here, is British author, journalist, and pacifist Vera Brittain (1893-1970). I draw on Brittain’s autobiographical trilogy Testament of Youth (1933), Testament of Friendship (1940), and Testament of Experience (1957), as well as on her 1920s and 1930s journalism in order to reveal how she waged “war” (her term) on Victorian womanhood. She unabashedly and relentlessly led the ranks of team “working mother” during the “mommy wars”of her day, showcasing through theory and by example unconventional approaches to middle-class motherhood. She believed, as she lived, that if mothers are to be completely realized and fulfilled individuals, they must engage in meaningful and remunerative occupations. Anne-Marie Slaughter’s 2012 Atlantic article “Why Women Still Can’t Have it All” and Sheryl Sandberg’s Lean In: Women, Work, and the Will to Lead (2013) tap, like Brittain’s work, into the zeitgeist of maternal anxiety, confusion, andchoice, producing wildly divisive reactions by readers and mothers eager to define andquery what it means to be a so-called “modern” and “good” mother. With reference to these contemporary debates, I argue that Brittain remains profoundly relevant to our understanding of twenty-first century maternal politics, and that career-driven mothers today may claim the unfinished business of her feminist agenda as their own.